Exploratory study on how advertising affects credit card usage of young professionals : the case of Singapore. - Goh, Yee Ping. (2008)
Our study seeks to establish if a relationship exists between the effectiveness of advertising and credit card usage among young professionals in Singapore. It also examines whether factors such as cardholders’ money ethics, acquisition and payment episodes have any moderating effects on this relationship.